2005
DOI: 10.1523/jneurosci.1912-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Heat Shock Protein 70: A Critical Component for Motoneuron Survival

Abstract: The dependence of developing spinal motoneuron survival on a soluble factor(s) from their target, muscle tissue is well established both in vivo and in vitro. Considering this apparent dependence, we examined whether a specific component of the stress response mediates motoneuron survival in trophic factor-deprived environments. We demonstrate that, although endogenous expression of heat shock protein 70 (HSP70) did not change during trophic factor deprivation, application of e-rhHsp70 (exogenous recombinant h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 74 publications
(95 reference statements)
2
95
0
Order By: Relevance
“…The evolutionarily conserved STI1, including its human homolog HSP70/HSP90 organizing protein (Hop), interacts with both HSP70 and HSP90 to facilitate the transfer of substrates, thus playing an important role in proper protein folding and maturation (Hernandez et al, 2002). The HSPs are abundantly expressed in both the cytoplasm and the nucleus (Honore et al, 1992;Lassle et al, 1997); however, growing evidence suggest that some HSPs, in particular HSP90 and HSP70, can be secreted by distinct cells (Eustace and Jay, 2004;Evdonin et al, 2006), including astrocytes (Guzhova et al, 2001;Robinson et al, 2005). Secreted HSP70 has been related to prevention of axotomy-induced death of spinal sensory and motor neurons (Houenou et al, 1996;Tidwell et al, 2004), as well as protection against light damage of photoreceptors (Yu et al, 2001) and enhancement of motoneuron survival in vivo during the period of naturally occurring programmed cell death (Robinson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The evolutionarily conserved STI1, including its human homolog HSP70/HSP90 organizing protein (Hop), interacts with both HSP70 and HSP90 to facilitate the transfer of substrates, thus playing an important role in proper protein folding and maturation (Hernandez et al, 2002). The HSPs are abundantly expressed in both the cytoplasm and the nucleus (Honore et al, 1992;Lassle et al, 1997); however, growing evidence suggest that some HSPs, in particular HSP90 and HSP70, can be secreted by distinct cells (Eustace and Jay, 2004;Evdonin et al, 2006), including astrocytes (Guzhova et al, 2001;Robinson et al, 2005). Secreted HSP70 has been related to prevention of axotomy-induced death of spinal sensory and motor neurons (Houenou et al, 1996;Tidwell et al, 2004), as well as protection against light damage of photoreceptors (Yu et al, 2001) and enhancement of motoneuron survival in vivo during the period of naturally occurring programmed cell death (Robinson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of CRTC3 in blood enhances the uncertainty about the exclusive role of CRTCs as CREB coactivators in the nucleus (30,31 ). A growing list of proteins have dual localization, being found in both the intracellular and the extracellular compartment (10,11,20 ). We herein demonstrate that CRTC3 can be found in the circulation and suggest that it is related to childhood obesity as a newly identified soluble protein.…”
Section: Discussionmentioning
confidence: 67%
“…It is also possible that Hsp70 induction may stimulate other systems that are responsible for cell survival after brain injury (Seidberg et al 2003;Robinson et al 2005). Cumulative indirect effects of Hsp70, such as suppression of apoptosis (Tidwell et al 2004), lysosome stabilization (Kirkegaard et al 2010), stimulation of the innate immune response (Johnson and Fleshner 2006;Gong et al 2009), suppression of the early preoligomeric stages of Aβ self-assembly (Evans et al 2006;Calderwood 2010), inhibition of proinflammatory signaling (Rozhkova et al 2010), and increase of survival of endogenous neural progenitor cells (Doeppner et al 2009) may account for the observed correlation.…”
Section: Discussionmentioning
confidence: 99%